Building Awareness of Financial Management Behavior Among Students - Izza Nikmatur Rokhmah; Detak Prapanca; Herlinda Maya Kumala Sari (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to examine the influence of fintech payments, financial socialization and financial experience on financial management behavior. This research uses quantitative descriptive methods. The population in this study were active students at Muhammadiyah University of Sidoarjo, totaling 12,730 students and used a purposive sampling technique. The sample was determined using the Slovin formula and a sample of 99 respondents was obtained. The research data source is primary data. The analysis technique uses Partial Last Square with Smart PLS 3.0. The research results show that fintech payment, financial experience and financial socialization partially have a significant effect on financial management behavior.